Dictionary of micro-toponyms of Ishtii-Khem village - Kuske, Viktoria (The New Research of Tuva, 2013)
Article by the schoolgirl from the village Ishtii-Khem in Ulug-Khem district of Tuva represents a project for the "My Earth” forum (campaign "Cher” – "The Earth”). Author composed a small dictionary of local micro-toponyms and made an effort to explain their origins.